2017
DOI: 10.1080/19390211.2017.1350246
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Red Gram (Cajanus cajan L.) Prebiotic Oligosaccharides in Wistar NIN Rats

Abstract: The hypolipidemic effect of red gram prebiotics of raffinose family oligosaccharides was studied in Wistar National Institute of Nutrition male rat strain. The study consisted of 36 rats randomly divided into three groups of 12 rats each. For 16 weeks, Group I was fed with the control diet; Group II was fed with a diet containing 3% standard raffinose as the reference group; Group III received the diet containing 3% red gram prebiotics. The results showed that the gain in body weight was low in the red gram pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Different types of lactose-derivatives such as GOS, lactosucrose, and tagatose can effectively inhibit the expression of fat-forming genes and enzymes, promote the combination of cholesterol and probiotics, reduce the cholesterol level, and promote the transformation of BA enzyme and lipid metabolism to regulate lipid level ( Nath et al., 2018 ). Red gram prebiotics can reduce the TG, TC, and HDL-C levels in hyperlipidemia-model rats ( Shakappa et al., 2018 ). By changing the composition of gut microbiota through prebiotics, the mediated effect of GLP-2 can improve the intestinal-barrier function, reduce the amount of endotoxin into the blood, and improve the metabolism of blood lipids ( Cani et al., 2009 ).…”
Section: Treatment Of Hyperlipidemia Targeted At Gut Microbiotamentioning
confidence: 99%
“…Different types of lactose-derivatives such as GOS, lactosucrose, and tagatose can effectively inhibit the expression of fat-forming genes and enzymes, promote the combination of cholesterol and probiotics, reduce the cholesterol level, and promote the transformation of BA enzyme and lipid metabolism to regulate lipid level ( Nath et al., 2018 ). Red gram prebiotics can reduce the TG, TC, and HDL-C levels in hyperlipidemia-model rats ( Shakappa et al., 2018 ). By changing the composition of gut microbiota through prebiotics, the mediated effect of GLP-2 can improve the intestinal-barrier function, reduce the amount of endotoxin into the blood, and improve the metabolism of blood lipids ( Cani et al., 2009 ).…”
Section: Treatment Of Hyperlipidemia Targeted At Gut Microbiotamentioning
confidence: 99%
“…Pigeon pea prebiotic fed groups showed improved lipid metabolism by decreasing serum triglycerides, total cholesterol, LDL cholesterol, and VLDL cholesterol in comparison with the control group. Hence, prebiotics can be a preventive measure for obesity and type 2 DM [19]. Therefore, the present study shows the effects of pigeon pea prebiotic oligosaccharide potential on gut microbiota, obesity, and type 2 DM in WNIN rats.…”
Section: Introductionmentioning
confidence: 56%
“…Many human involved researches have manifested that the intake of de nite prebiotic supplements will remarkably change the use of intestinal micro ora. In an earlier study, we have reported the hypolipidemic action of pigeon pea (Cajanus cajan L.) prebiotic oligosaccharides in WNIN rats [19]. A research was organized to assess the outcome of 3 differing prebiotics, i.e., indigestible dextrin, α-cyclodextrin, and dextran on human gut micro ora.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage selection of Lupinus albus α-galactooligosaccharides (LA-GOS), used in the treatment, was determined according to the literature [ 47 , 48 , 49 , 50 , 51 , 52 ]. To select the therapeutic dosage, we considered the following theoretical aspects: the evaluated experimental model, its demonstrated effect in the model, and the dosage conversion according to the selected species (mice model).…”
Section: Methodsmentioning
confidence: 99%